2010
DOI: 10.1155/2011/606514
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture on the Endometrial Morphology, the Serum Estradiol and Progesterone Levels, and the Expression of Endometrial Leukaemia‐inhibitor Factor and Osteopontin in Rats

Abstract: Although it is well known that acupuncture has beneficial effects on a variety of medical conditions especially in pain relief, nausea, and vomiting, it remains controversial whether it has positive impact on the female reproduction. The present study aimed to evaluate whether the following endometrial receptivity factors: the endometrial morphology, the hormone concentrations, and the protein expression of endometrial leukaemia-inhibitory factor (LIF) and osteopontin (OPN) could be improved by the acupuncture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Two interventions (pharmacotherapy and endometrial scratching) have been suggested to improve endometrial receptivity among patients with recurrent implantation failure [16]. Pharmacologic approaches include supplementation with aspirin, estrogens, sildenafil citrate, or rhGH, which might facilitate endometrial development by dominant hormonal modulators, thereby promoting endometrial blood flow perfusion and/or secretion of various cytokines such as VEGF and IGF-1 [17,18]. The effects of endometrial scratching can be attributed to an inflammatory reaction in response to injury, leading to the development of endometrium; however, this approach has the disadvantages of pain and risk of infection [16].…”
Section: Discussionmentioning
confidence: 99%
“…Two interventions (pharmacotherapy and endometrial scratching) have been suggested to improve endometrial receptivity among patients with recurrent implantation failure [16]. Pharmacologic approaches include supplementation with aspirin, estrogens, sildenafil citrate, or rhGH, which might facilitate endometrial development by dominant hormonal modulators, thereby promoting endometrial blood flow perfusion and/or secretion of various cytokines such as VEGF and IGF-1 [17,18]. The effects of endometrial scratching can be attributed to an inflammatory reaction in response to injury, leading to the development of endometrium; however, this approach has the disadvantages of pain and risk of infection [16].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that EA can modulate sympathetic nerve activities to modulate the neuroendocrinological function of ovaries. Further, acupuncture at the bilateral SP6, LR3, and CV3 acupoints significantly decreased the serum estradiol levels and endometrial leukaemia-inhibitor factor (LIF) and Osteopontin (OPN) expression and enhanced glandular development in the clomiphene citrate-induced rat model during the implantation period (Fu et al, 2011). Therefore, acupuncture improved endometrial receptivity, which is beneficial to female reproduction.…”
Section: Acupuncture Stimulation and Female Hormonesmentioning
confidence: 97%
“…The principle of AP was initially based on the balance of Ying and Yang in TCM but today it is mostly thought as sympathetic parasympathetic interaction [4] . According to this method there are meridian systems transporting the life energy which is thought to be regulating the body functions by connecting and communicating specific organs in the body and these meridians intersect in several points on the skin [5] . Most diseases and injuries are caused by problems in the flow and balance of the life energy.…”
Section: Introductionmentioning
confidence: 99%